Ag2Se/SnTe nanorod as potential candidate for energy conversion system developed via hydrothermal route. Issue 4 (15th February 2023) - Abdullah, Muhammad; Ansari, Mohd Zahid; Ahamd, Zahoor; John, Peter; Manzoor, Sumaira; Shawky, Ahmed M.; Hegazy, H.H.; Chughtai, Adeel Hussain; Ashiq, Muhammad Naeem; Taha, T.A.
Abstract: It is vital to develop an effective energy storage system for storing energy sources, particularly renewable energy sources, which have grown substantially in the preceding decade. The development of effective electrode materials can aid in the resolution of such problem. Metal chalcogenides have shown promise in a various sector, consisting of energy conversion and storage. Herein, a novel hierarchical Ag2 Se/SnTe nanocomposite is fabricated by in situ one step hydrothermal approach for supercapacitor applications. The various analytical techniques were employed for the structural, morphological, and textural properties of fabricated electrocatalyst material. The result of electrochemical studies suggests that the Ag2 Se/SnTe exhibited the specific capacitance (Cs ) of 1560.32 F g −1, energy density (Ed ) of 99.76 Wh kg −1, power density (Pd ) 1356.8 W kg −1 @ 4 A g −1 and retention capacitance of 95% over 5000 cycle under 2.0 M KOH. This research not only demonstrates the enormous potential of the readily available Ag2 Se/SnSe composite, but also a revolutionary approach for producing, high-performance and low-cost composite materials for many other energy applications.